Ox-LDL Promotes Migration and Adhesion of Bone Marrow-Derived Mesenchymal Stem Cells via Regulation of MCP-1 Expression - Fenxi Zhang; Congrui Wang; Huaibin Wang; Ming Lu; Yonghai Li; Huigen Feng; Juntang Lin; Zhiqing Yuan; Xianwei Wang (Mediators of Inflammation)
Bone marrow-derived mesenchymal stem cells (bmMSCs) are the most important cell source for stem cell transplant therapy. The migration capacity of MSCs is one of the determinants of the efficiency of MSC-based transplant therapy. Our recent study has shown that low concentrations of oxidized low-density lipoprotein (ox-LDL) can stimulate proliferation of bmMSCs. In this study, we investigated the effects of ox-LDL on bmMSC migration and adhesion, as well as the related mechanisms. Our results show that transmigration rates of bmMSCs and cell-cell adhesion between bmMSCs and monocytes are significantly increased by treatments with ox-LDL in a dose- and time-dependent manner. Expressions of ICAM-1, PECAM-1, and VCAM-1 as well as the levels of intracellular Ca2+ are also markedly increased by ox-LDL in a dose-dependent manner. Cytoskeleton analysis shows that ox-LDL treatment benefits to spreading of bmMSCs and organization of F-actin fibers after being plated for 6 hours. More interestingly, treatments with ox-LDL also markedly increase expressions of LOX-1, MCP-1, and TGF-β; however, LOX-1 antibody and MCP-1 shRNA markedly inhibit ox-LDL-induced migration and adhesion of bmMSCs, which suggests that ox-LDL-induced bmMSC migration and adhesion are dependent on LOX-1 activation and MCP-1 expression.